Polyamide thin film composite membrane using mixed amines of thiourea and m-phenylenediamine. Issue 67 (24th July 2015) - Li, Wei; Lou, Liya; Hai, Yuyan; Fu, Changxin; Zhang, Jinli
<x xml:space="preserve">Abstract</x> Polyamide TFC membranes were prepared on porous polyethersulfone support via interfacial polymerization between trimesoyl chloride and an amine mixture. Under optimal conditions, the membranes show good separation performance and excellent chlorine resistance.